Socio- Political Issues and Resistance in Mirza Waheed‟s “The Book of Gold leaves” - Malhotra, Ruchi; Ahmed Naik, Gowher (International Journal of Psychosocial Rehabilitation, 2021)
The war continually turns standard morality and nearly everybody and every one social establishment the wrong way up. During this case, the Jammu and Kashmir conflict is not any exception; everybody living during this conflict zone has intimate the harshness of destroyed from their own eyes. Kashmir is a land with many military forces, suffering terribly and its people suffering terribly as a result of military action. Mirza Waheed who is one of the traditional writers of modern times talking about Kashmir is captures the tragic lives of traumatized people who are forced to live difficult lives. He gives a voice to the indescribable wonders that are part of the Kashmir war. Waheed writes about the passionate love of Kashmir and its people and gives a glimpse of many people of their fragile, amazing lives tragically wounded in this way by the conundrum. A book of gold leaves It is associated with the violence and violence that is rampant in Kashmir and illustrates the pain and suffering of the oppressed Kashmir is who have suffered since the beginning of the uprising, uprisings, and so on.We have a love story in the middle of the narrative. Set in the heart of the city of Srinagar, the novel focuses on how a better and more peaceful way of life ends for Faiz and Roohi, two lovers who dream of a happy life. The events and events around them represent modern-day Kashmir. This paper looks at various events and episodes in the novel, focusing on Waheed’s attempt to give a voice to the oppressed and the oppressed and to create a counter-argument to expose Kashmir’s elaborate stories.